A Bilocular Radicular Cyst in the Mandible with Tooth Structure Components Inside. (3rd September 2019) - Noda, Akari; Abe, Masanobu; Shinozaki-Ushiku, Aya; Ohata, Yae; Zong, Liang; Abe, Takahiro; Hoshi, Kazuto
Abstract : Background . A radicular cyst is the most common odontogenic cyst of inflammatory origin. Radiographically, it commonly demonstrates clear unilocular radiolucency; radicular cysts with multilocular radiolucency are quite rare. Case Presentation . A 64-year-old Japanese man who presented with a bilocular radiolucent lesion in his left mandible was referred by a dental clinic to our oral and maxillofacial surgery department. He had no particular subjective symptoms. Orthopantomography and computed tomography (CT) revealed an18   mm × 15   mm lesion with well-defined bilocular radiolucency in the left mandible expanding from the distal side of a canine tooth to the bottom of the 2nd premolar. The lesion included the roots of the 1st and 2nd premolars. The root of the 2nd premolar showed knife-edge resorption. Although the 1st premolar was nonvital, the 2nd premolar was a vital tooth. As differential diagnoses, a radicular cyst, ameloblastoma, odontogenic keratocyst, pseudocyst, and others might be considered. We performed a total resection of the bilocular lesion and diagnosed the lesion as a radicular cyst with tooth structure components inside. The tooth structure components represented lamellar structures of cementum; they were located only in the proximal part (under the 1st premolar) of the lesion. The distal part of the lesion presented distinctive inflammation without tooth structure components. Conclusion . We encountered a rare case of a bilocular radicular cyst with tooth structure components inside.